Археологические данные о связях славян и степного населения в VII-VIII вв. - Приходнюк, О.М. (Материалы по археологии, истории и этнографии Таврии, 1996)
This article is devoted to the analysis of archaeological data concerning an important historic problem - interaction of the Slavs and the steppe population in the 7th - 8th centuries. In Slav settlements situated in frontier districts of European forest-steppe and steppe they found ÿurta-shaped buildings (Osipovka, Bogatoe, Chernechina) and houses on socles (Majorka), which were characteristic for the steppe dwellers. But not only steppe dwellers penetrated the Slav communities, the Slav population also intruded different ethnical habitat. It is testified in the archaeological materials of Dmitriev cemetery of Saltovo culture and of many cemeteries of Avar period in Hungary (Oroslan, Pokasenetk, others). In middle parts of the Danube region they excavated quadrangular dug-outs with pottery of Slav appearance (Hidveg-pust, Shai-Lotor and others). It is beyond doubt, that settled nomads were equal in rights with the members of Slav communities, but the Slavs in Avar communes were subordinated.